2022
DOI: 10.3390/su14031178
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media to Promote Sustainable Fashion and Benefit Communications: A Data-Mining Approach

Abstract: Numerous brands utilize social media to capture consumers’ interests while promoting their sustainability goals. To understand how sustainable fashion brands communicate with their consumers, this study explored the visual and textual information sustainable fashion brands post on social media. Data were collected from sustainable fashion brands’ social media pages, and a total of 1525 images and captions and 140,735 comments were analyzed. By employing color theory and the theory of speech acts, HSV color ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 43 publications
0
11
0
2
Order By: Relevance
“…The business environment is changing very quickly with the rapid adoption of social media and the development of mobile technologies [26]. Social media platforms enable interactive experiences between brands and consumers [27]. As more businesses feel the need to join social media platforms, the social media industry is expected to continue to show a growing trend.…”
Section: Factor Most Significant Challenge In Abstractmentioning
confidence: 99%
“…The business environment is changing very quickly with the rapid adoption of social media and the development of mobile technologies [26]. Social media platforms enable interactive experiences between brands and consumers [27]. As more businesses feel the need to join social media platforms, the social media industry is expected to continue to show a growing trend.…”
Section: Factor Most Significant Challenge In Abstractmentioning
confidence: 99%
“…В зарубежных работах формирование профессиональной речевой культуры как качества профессионала и как часть профессиональной культуры не рассматривается; данное явление рассматривается в контексте профессионального развития, внимание данному явлению уделяется в редких случаях с позиций культуры речи [411], с позиций теории речевых кодов в межкультурной коммуникации для говорящих на неродном языке либо коммуникативных способностей [382; 407]. Также в работах описывается роль культуры речи в развитии способности к межкультурному взаимодействию [422] и устойчивости, безопасности в условиях профессиональной деятельности [415; 416], что позволяет человеку действовать в будущей профессии более эффективно [367]; кроме того, в работах подчеркивается необходимость учитывать культурный компонент, дающий обучающимся возможность повысить осознание тесной связи между людьми и природой в культурном плане, описывается влияние профессиональной и этнокультурной идентичности субъектов образовательного процесса на формирование мировоззрения [371], культурных ценностей и философии образования, т.е. в переосмыслении ценностей, убеждений, мировоззрения, в обмене смыслами играет важную роль национальная картина мира, отраженная также и в языке субъекта познания.…”
Section: пятый контекст профессиональной речевой культурыречевая проф...unclassified
“…Zhao et al analyzed the use of social media by sustainable fashion brands to communicate with consumers and promote their sustainability goals. Through a content analysis of the Instagram pages of the brands Verlaine, Patagonia, and Stella McCartney, the researchers found that posts with expressive and directive advertising were more likely to receive comments and likes from users (Zhao et al, 2022). This research provides context for user response to social media marketing and how different approaches to social media marketing can impact consumer engagement.…”
Section: Introductionmentioning
confidence: 99%